LINGKUNGAN EKSTERNAL,,FAKTOR INTERNAL,DAN ORIENTASI PASAR PENGARUHNYA TERHADAP KINERJA PEMASARAN - Praetya, Dicky Imam (Master of Management Diponegoro University, 2002)
The positive effect of market orientation on business performance had been well documented. However, the identification processes of which factors driving the degree of market orientation and its relation with performance have been the subject of long debate. Some scholars proposed that environmental conditions moderate market orientation-performance link, while the others found empirical evidence that environmental factors can be treated as antecedents of market orientation. Thereby the present study is intended to develop an integrative model of market orientation in the context of business units of Bank Bali. The model describe that external environment and internal factors are hypothesised as antecedents of market orientation. The model subsequently delineate market orientation - marketing performance link. Bank Bali is chosen due to recent conditions can offer an ideal venue for testing the models. In this study, the external environment is conceptualized along the dimensions of dynamism and munificence, while internal factors are comprised of the dimensions offormalization and centralization. Furthermore, market orientation consists of three behavioural components: customer orientation, competitor orientation, and interfunctional coordination, where marketing performance incorporates efficiency, effectiveness, and adaptability criteria into the measurement. The sampling frame of this research consist of senior managers of 155 business units of Bank Bali whom are randomly selected. Structural Equation Modeling (SEM) which is run by Amos software is employed to analyze the data. The result shows that environmental dynamism positively affects the degree of market orientation while each of environmental munificence, formalization, and centralization has negative impact. Furthermore, market orientation is proven to have a positive effect on marketing performance. The empirical findings suggest that senior managers of business unit of Bank Bali should strive to improve the market orientation of their business units in their efforts to attain higher performance by analyzing the external context in which the business unit operates and the internal context beforehand. The theoretical implications and suggestions for future research are also discussed.